The Night Sky Companion - Tammy, Plotner (Springer, 2017)
The The Night Sky Companion is far more than just an observing guide. It is a year’s journey into the science and facts of astronomy and space travel, along with some of its history and the and the men and women who made it. If you’re a sky watcher equipped with any kind of astronomical telescope, binoculars, or even just your eyes, you are sure to find this book absolutely fascinating.